2020
DOI: 10.3390/su12041583
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital, Social Capital, and Farmers’ Credit Availability in China: Based on the Analysis of the Ordered Probit and PSM Models

Abstract: Rural credit is very important to the increase of farmers' income and the development of rural economy, and it has attracted wide attention from scholars. Many scholars have paid attention to the impact of social capital on farmers' credit availability, but the research conclusions have not yet been unified. In addition, human capital is also one of the important factors that scholars pay attention to. However, the research mainly focuses on farmer education and pays less attention to their health. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Despite many smallholder farmers possessing the capacity for larger-scale operations, credit limitations often restrict their ability to invest and expand [36]. Numerous scholars have studied the factors affecting the availability of credit to farmers, identifying education level, health status, work experience, and financial condition as significant influencers [37]. With the advancement of information technology, digital technology has also increasingly become a critical factor impacting farmers' access to credit [38].…”
Section: Digital Technology Use Credit Accessibility and Land Transfe...mentioning
confidence: 99%
“…Despite many smallholder farmers possessing the capacity for larger-scale operations, credit limitations often restrict their ability to invest and expand [36]. Numerous scholars have studied the factors affecting the availability of credit to farmers, identifying education level, health status, work experience, and financial condition as significant influencers [37]. With the advancement of information technology, digital technology has also increasingly become a critical factor impacting farmers' access to credit [38].…”
Section: Digital Technology Use Credit Accessibility and Land Transfe...mentioning
confidence: 99%
“…The most important two steps in PSM includes 22 • Propensity scores are obtained using the logit regression method, that is, probability of the individual in the treatment group, considering different covariates.…”
Section: Step 6 Estimating the Effects Of An Interventionmentioning
confidence: 99%
“…In addition, some scholars have found that rural credit is conducive to increasing farmers' income and improving rural economic level. Liu et al [18] found that the education level and health level of farmers will affect the availability of rural credit. In addition, social capital also has an impact on whether farmers can obtain loans, such as interpersonal capital and political relationship capital.…”
Section: Related Workmentioning
confidence: 99%